A Case Report of Tubercular Constrictive Pericarditis - Basak, Rajib Kumar; Aftabuddin, Md; Adhikary, Asit Baran; Khan, Omar Sadeque; Rahman, Khan Mohammad Amanur (University Heart Journal, 2015)
Diagnosis of Constrictive pericarditis is sometimes become difficult because that requires a high degree of clinical suspicion due to nonspecific sign and symptoms. But in endemic area like our country the presentation of tubercular constrictive pericarditis is common. Here we report a case of 28 year Bangladeshi male with tubercular constrictive pericarditis presenting with progressive exertional dyspnea, ankle edema, puffyness of face, dry nonproductive caugh. After physical examination and investigation, the patient was diagnosed as constrictive pericarditis. Patient was previously diagnosed as a tubercular patient and still now on antitubercular cat-1 chemotherapy. So finally diagnosis becomes tubercular constrictive pericarditis. After improvement of the symptoms with medical treatment, the definitive surgical intervention, pericardiectomy done. Then removed pericardial tissue was sent for histopathological examination and histopathological report confirmed the diagnosis of tubercular pericarditis. This case is a late presentation of extrapulmonary manifestation of pulmonary tuberculosis, which is present as a consequence or, complication of pulmonary tuberculosis. So, early diagnosis and treatment is very much important in this case to prevent late consequence like tubercular constrictive pericarditis. University Heart Journal Vol. 10, No. 1, January 2014; 42-44